1998
DOI: 10.1021/jp9809787
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy and Dynamics of Nanometer-Sized Noble Metal Particles

Abstract: Electron-phonon coupling in 11 ( 2 nm diameter Au particles and 10 ( 3 nm and 50 ( 10 nm Ag particles has been examined by ultrafast pump-probe spectroscopy. The observed relaxation times are strongly dependent on the pump laser power. At the lowest pump powers used, the time constants for relaxation are 0.8 ( 0.1 ps for the 11 nm Au particles, 1.1 ( 0.1 ps for the 10 nm Ag particles, and 1.0 ( 0.1 ps for the 50 nm Ag particles. The measured relaxation times are similar to those for bulk metals, which implies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
479
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 337 publications
(524 citation statements)
references
References 47 publications
(136 reference statements)
43
479
2
Order By: Relevance
“…[25][26][27] The electron-phonon coupling was found to be size 3,7 and shape 7,8 independent for gold nanoparticles in the size range from 8 to 120 nm. The measured electron-phonon relaxation times depend on the laser pump power 2,3,7 and are on the order of a few picoseconds (1-4 ps). [1][2][3][4][5][6][7][8][9][10][11][12][13] The results obtained for the nanoparticles furthermore compare well with the electronphonon coupling constant measured for bulk gold 28 using similar time-resolved laser techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] The electron-phonon coupling was found to be size 3,7 and shape 7,8 independent for gold nanoparticles in the size range from 8 to 120 nm. The measured electron-phonon relaxation times depend on the laser pump power 2,3,7 and are on the order of a few picoseconds (1-4 ps). [1][2][3][4][5][6][7][8][9][10][11][12][13] The results obtained for the nanoparticles furthermore compare well with the electronphonon coupling constant measured for bulk gold 28 using similar time-resolved laser techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Faster electronic relaxation is attributed to greater electron-phonon coupling [141]. The transfer of energy between hot electrons and the nanoparticles can be observed as coherent vibrational oscillations which are indicative of the breathing modes of the nanoparticle lattice [57,152,153]. The amplitude of the coherent oscillations of HGNs can be correlated to aspect ratio since amplitude is inversely proportional to the electron-phonon coupling constant g [153,154].…”
Section: Electron Dynamicsmentioning
confidence: 99%
“…It has been reported that low aspect ratio nanoparticles have g values comparable to their solid counterparts while high aspect ratio ones have enhanced g values [14,85,140,152,182]. In this work, as the aspect ratio increased from 3.5 to 9.5, the g value increased from 1.67 × 10 16 ± 0.22 to 3.33 ± 0.45 × 10 16 W m −3 k −1 , while solid NPs maintained an average g of 1.90 ± 0.20 × 10 16 W m −3 k −1 over a range of diameters (20,40, and 80 nm) [149].…”
Section: The Influence Of Laser Mode and Powermentioning
confidence: 99%
See 1 more Smart Citation
“…It can provide 10-fold to 100-fold higher SERS signals than the similar Au NPs, which is mainly due to its d-s band gap, is in the ultraviolet (UV) region, giving rise to less damping of the plasmon mode. 30,31 Accordingly, in the present study, we applied SERS technique to the sensitive and selective detection of heparin based on antiaggregation of 4-MPY functionalized Ag NPs upon the presence of protamine. Protamine is a kind of natural peptide with polypositive ion, which has ∼20 charges; 32 its special structure could lead to the aggregation of 4-MPY functionalized Ag NPs, thus resulting in the changes in colors, surface plasmon resonance absorption and Raman intensity of 4-MPY.…”
Section: ■ Introductionmentioning
confidence: 99%